2017
DOI: 10.1016/j.gendis.2017.06.002
|View full text |Cite
|
Sign up to set email alerts
|

Association analysis of FTO gene polymorphisms and obesity risk among Egyptian children and adolescents

Abstract: Obesity is a common disorder that has a significant impact on human health as it may lead to many serious diseases and sometimes morbidity. Previous genome-wide association studies (GWAS) confirmed that there is a relationship between some variants in the first intron of the fat mass and obesity associated (FTO) gene and obesity in adults and children in different ethnic groups. In our study, the association of the FTO rs9939609 and rs17817449 variants with obesity was investigated in Egyptian children and ado… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 41 publications
0
23
0
3
Order By: Relevance
“…41,42 In Egypt, however, no risk was found between obesity and rs9939609 in 200 children and adolescents. 43 In a New Zealand-based study, no significant difference was found between BMI z-score and FTO-rs9939609 and MC4R-rs17782313 and between body fat percentage and FTO-rs1421085 in European children. 44 In a study involving 580 children in Mexico, a positive relationship was found between blood pressure and rs9939609, rs17782313, while no significant correlation was found between total cholesterol and HDL cholesterol.…”
Section: Discussionmentioning
confidence: 90%
“…41,42 In Egypt, however, no risk was found between obesity and rs9939609 in 200 children and adolescents. 43 In a New Zealand-based study, no significant difference was found between BMI z-score and FTO-rs9939609 and MC4R-rs17782313 and between body fat percentage and FTO-rs1421085 in European children. 44 In a study involving 580 children in Mexico, a positive relationship was found between blood pressure and rs9939609, rs17782313, while no significant correlation was found between total cholesterol and HDL cholesterol.…”
Section: Discussionmentioning
confidence: 90%
“…The disease is highly prevalent in Egypt with an estimated prevalence of approximately 61-70% of the adult population with a higher percentage in females more than males. Obesity is also considered as one of the top contributors to mortality among Egyptians due to the associated comorbid diseases as hypertension and diabetes (6) .…”
Section: Discussionmentioning
confidence: 99%
“…No association with obesity phenotype in Egyptian adolescents and children; however, the presence of the risk allele was linked to higher LDL cholesterol (n=200) 42…”
Section: Introductionmentioning
confidence: 93%
“… Neuropeptide Y ( NPY ) 7q15.1This peptide regulates energy homeostasis thought binds to its receptor on PVN .rs53587023717-bp deletion at 5’UTR0.00039Observed in one Mexican American family (n=934) 58 Fat Mass Obesity-Associated gene ( FTO ) 16q12.2Demethylation enzyme involved in controlling of energy homeostasis, DNA methylation and abiogenesisrs9939609Intron 10.340No association with obesity phenotype in Egyptian adolescents and children; however, the presence of the risk allele was linked to higher LDL cholesterol (n=200) 42Associated with morbid obesity risk in the Brazilian adults (n=239) and Mexican population (n=1,156) 13,44…”
Section: Introductionmentioning
confidence: 99%